Ideology in public comments towards news about Jakarta election in social media - Liza Halimatul Humairah; Agustina Agustina; Ngusman Abdul Manaf (Fakultas Ilmu Pendidikan UNP)
The 2017 of Jakarta Election is not only enlivened by the comments of politicians and experts , but also followed by the general public in a critical, obscene, and massive way. This study aimed to reveal the ideology in public opinions about the discourse of Jakarta election at social media. This research used qualitative-descriptive approach with content analysis method, and based on the critical discourse analysis theory by Norman Fairclough. The result of the research showed (1) about 57.4% of public opinions represent ideology of Islamic religion by raising the issue of the importance of Aqeedah, Sharia, and morals for leaders, through vocabularies like the similar faith, fellow moeslems, humane, and dirt, (2) a number of 34.8% show the ideology of secularism with the issue of electing the government leaders not a religious leader through the use of vocabularies such as performance, don’t, clean, not corrupt; while (3) just 7.8% represent the ideology of liberalism with the issue such as no offense for the public to choose their leader through the use of vocabularies such as freedom, logical thinking, realistic, and common sense.